STUDY OF THE CRUDE BIRTH RATE AND DELIVERY CONDITION AMONG THE QASHQAI TRIBE, SOUTHERN IRAN - M. Motabar; M. Mohseni (Tehran University of Medical Sciences, 1976)
On the basis of a cross-sectional demographic survey that was conducted among the Qashqai Tribe of southern Iran in 1973, the crude birth rate was estimated at 48.2 per thousand per year. The most productive age groups, was 25-29 years. Forty-nine, point seven per cent (49.7%) or about one half of the total births occurred among married women aged 20 to 29 years Eighty-seven point three per cent (87.3%) of the deliveries took place in tents, only one per cent at maternity hospitals. Ninety point one per cent (90.1%) of babies were delivered with the help of relative and friends, while only 6.9 per cent of all deliveries took place with the aid of midwives. Eighty-nine point seven per cent (89.7%) of deliveries were performed without medical expenses.